Prevalence and spatial distribution of Entamoeba histolytica/dispar and Giardia lamblia among schoolchildren in Agboville area (Côte d'Ivoire). - Mamadou Ouattara; Nicaise A N'guéssan; Ahoua Yapi; Eliézer K N'goran (Public Library of Science (PLoS), 2010)
BACKGROUND: New efforts are being made to improve understanding of the epidemiology of the helminths and intensifying the control efforts against these parasites. In contrast, relatively few studies are being carried out in this direction for the intestinal protozoa. To contribute to a better comprehension of the epidemiology of the intestinal protozoa, prevalence, and spatial distribution of Entamoeba histolytica/dispar and Giardia lamblia, and their association with drinking water supplies, were determined in the Agboville department in southeast Côte d'Ivoire. METHODS/FINDINGS: Stool samples were taken from more than 1,300 schoolchildren in the third year of primary education (CE1) from 30 primary schools and preserved in SAF (sodium acetate-acetic acid-formalin). The samples were analyzed by formalin-ether concentration. Then, a survey questionnaire addressed to schoolchildren and school directors was used to collect data on water supplies. Prevalence of E. histolytica/dispar and G. lamblia were, respectively, 18.8% and 13.9%. No particular focus zone was observed in the spatial distribution of the two species. Significant negative association was observed between use of tap water and high prevalence of E. histolytica/dispar infection (OR = 0.83, p = 0.01). High prevalence of G. lamblia infection was positively associated with use of ponds as the source of drinking water (OR = 1.28, p = 0.009). CONCLUSION: These two species of pathogenic protozoa are present with substantial prevalence in this area of Côte d'Ivoire. Although their spatial distribution is not focused in any one place, determination of the population segments with the highest levels of infection will help to target the chemotherapeutic fight. To reinforce treatment with chemotherapeutic agents, tap water should be made available in all the localities of this area.